OFFICE OF RELIGIOUS AFFAIRS BANAWA'S EFFORTS IN MINIMIZING STUNTING CASES IN DONGGALA REGENCY - Susilawati, Susi; Nokoe, Nurhayati Sutan; Pusadan, Sulwan; Nurman, Ilham (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
This article is based on research entitled